A Stylistic Analysis of Nature in Two Selected, English and Arabic, Pastoral Poems - Mohammed Hussein, Abbas; Al-Saidi, Abdali (Al-Adab Journal, 2024)
Since stylistics is concerned with studying styles, the present paper is an analysis of the styles in selected poems. Style is grasped by analyzing the choice and use of stylistic devices; therefore, this study investigates the lexical items and the figures of speech in two English and Arabic pastoral poems, namely Matthew Arnold’s The Scholar Gipsy and Kahlil Gibran’s Al-Mawakib. These poems share the same theme which is nature. Both idealize nature by praising it as being a source of imagination and inspiration. Yet, the poems also describe a city in a different description. Therefore, contrast is the style adopted in pastoral poetry and it is achieved by manipulating some stylistic devices. The study adopts Leech and Short’s (2007) checklist of stylistic markers as a framework for analysis. The findings of the analysis show great similarities in using the same stylistic devices in a contrastive manner in both poems with differences only in the frequency rates.